Economic Union Between Nations and the Location of Industries - Giersch, Herbert (Review of Economic Studies, 1949)
Journal Article Economic Union Between Nations and the Location of Industries Get access Herbert Giersch Herbert Giersch Münster and London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 17, Issue 2, 1949, Pages 87–97, https://doi.org/10.2307/2295866 Published: 01 January 1949